Nematodes of Backyard Deciduous Fruit Trees in Florida - Jimmy R. Rich; Robert A. Dunn; Peter C. Andersen (EDIS)
ENY-055, a 6-page illustrated fact sheet by Jimmy R. Rich, Robert A. Dunn, and Peter C. Andersen, provides an introduction to nematodes for the home owner, with sections discussing why nematodes are a pest, what they do to fruit crops, what kinds of nematodes affect fruit trees in Florida, how to tell if a problem comes from nematodes, how to manage nematodes, and key considerations. Includes a table of fruit crops and nematodes most likely to affect them in North Florida. Published by the UF Department of Entomology and Nematology, December 2006.